Extractive Content and Antioxidant Activity of Cajuput Bark (Melaleuca cajuputi Powell) - Bagus Praditya Harliando; Ganis Lukmandaru; Noor Khomsah Kartikawati (Wood Research Journal, 2024)
Both wood and non-wood industries generate large amounts of residues from processes like bark peeling and removal. In the cajuput oil industry, the waste products include distillation residues and cajuput bark. The diverse extractives and chemical components found in cajuput bark have the potential for enhanced value through various applications. This study aimed to determine the chemical components, extractive content (EC), and percentage inhibition of antioxidant activity (%IAA) of cajuput bark extract to explore more effective uses of this byproduct. Cajuput bark (Melaleuca cajuputi Powell) was sourced from a 26-year-old cajuput stand in Paliyan, Gunungkidul. The bark powder was extracted using a methanol-water solvent mixture at concentrations of 40% and 80%. Extraction was conducted in water baths at temperatures of 60°C and 100°C for 120 minutes. GC-MS identified several chemical components in the methanol extract of cajuput bark, including sugars (erythritol, D-arabinose, D-lyxose, adonitol, d-galactose, D-glucitol, and L-rhamnose), fatty acids (lactic acid, glycerol, glyceric acid, malic acid, and palmitic acid), and phenolic derivatives (gallic acid and protocatechuic acid). The average extractive content of the methanol extract of cajuput bark was 4.07%, and the percentage inhibition of antioxidant activity was 40.26%.